The Effect of the Application of the Nature of Science (NOS) Learning Model on Student Learning Outcomes - Nursalam Matondang; I Kusumawati; Eka Murdani (International Journal of Multi Discipline Science, 2020)
This study aimed to show the effect of implementing the Nature of Science (NOS) learning model on student learning outcomes. This type of research was a quantitative study with a sampling technique that is purposive sampling and a research design in the form of an experimental class and a control class. Based on statistical analysis using the SPSS application, it was identified that the data presented is normally distributed so that the data analysis in the next step used the parametric statistical T-test where it was found that sig 0.000 is smaller than 0.05, so H0 is rejected and Ha is accepted, which means that there was a significant effect on the learning outcomes of the experimental class students before and after the NOS learning model was applied to the Static Fluid material. The data collection instrument in this study was in the form of pre-test and post-test question sheets. After the data were analyzed using the effect size equation and it was found that the NOS learning model in the experimental class and control class had a difference of 1.681 with high criteria.